AglR is required for addition of the final mannose residue of the N-linked glycan decorating the Haloferax volcanii S-layer glycoprotein - Kaminski, Lina; Guan, Ziqiang; Abu-Qarn, Mehtap; Konrad, Zvia; Eichler, Jerry (Biochimica et biophysica acta, 2012)
Recent studies of Haloferax volcanii have begun to elucidate the steps of N-glycosylation in Archaea, where this universal post-translational modification remains poorly described. In Hfx. volcanii, a series of Agl proteins catalyzes the assembly and attachment of a N-linked pentasaccharide to the S-layer glycoprotein. Although roles have been assigned to the majority of Agl proteins, others await description. In the following, the contribution of AglR to N-glycosylation was addressed. A combination of bioinformatics, gene deletion, mass spectrometry and metabolic radiolabeling served to show a role for AglR in archaeal N-glycosylation at both the dolichol phosphate and reporter glycoprotein levels. The modified behavior of the S-layer glycoprotein isolated from cells lacking AglR points to an involvement of this protein in N-glycosylation. In cells lacking AglR, glycan-charged dolichol phosphate, including mannose-charged dolichol phosphate, accumulates. At the same time, the S-layer glycoprotein does not incorporate mannose, the final subunit of the N-linked pentasaccharide decorating this protein. AglR is a homologue of Wzx proteins, annotated as flippases responsible for delivering lipid-linked O-antigen precursor oligosaccharides across the bacterial plasma membrane during lipopolysaccharide biogenesis. The effects resulting from aglR deletion are consistent with AglR interacting with dolichol phosphate-mannose, possibly acting as a dolichol phosphate-mannose flippase or contributing to such activity. Little is known of how lipid-linked oligosaccharides are translocated across membrane during N-glycosylation. The possibility of Hfx. volcanii AglR mediating or contributing to flippase activity could help address this situation. ► In cells lacking AglR, glycan-charged dolichol phosphates accumulate. ► In ΔaglR cells, the final subunit of the N-linked pentasaccharide is absent. ► AglR is a homologue of Wzx, thought to ‘flip’ lipid-linked glycans in bacteria.